Hermeneutics and the Debate on Homosexuality in Africa - Bongmba, Elias K. (Religion & theology, 2015)
In this essay, I discuss hermeneutical approaches to the debate on homosexuality in the African context. I argue that the hermeneutics of Rudolf Bultmann offers a way of understanding the debate. I start with a general discussion of the response to homosexuality in Africa and follow that with a narration of perspectives from church leaders in Africa and proceed to discuss the work of Bultmann and in the last section apply the hermeneutical insights to point a way forward.